The Effectiveness of Positive Psychology Intervention on Academic Well-Being, Academic Emotions, and Academic Vitality in Lower Secondary School Students in Tabriz - Zahedan Zinjanab, Kobra; Hosseininasab, Seyed Davood; Azmoudeh , Masoumeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The present study was conducted with the aim of determining the effectiveness of a positive psychology intervention on academic well-being, academic emotions, and academic vitality in lower secondary school students in Tabriz.Methods and Materials: The research method was quasi-experimental using a pretest-posttest design with a control group. The statistical population included female students in the lower secondary level of District 3 in Tabriz. To select the sample, the questionnaires of academic well-being, academic emotions, and academic vitality were administered to 600 students from the mentioned population who had been selected using a cluster random sampling method. Then, 60 students who had the lowest scores on all three questionnaires were selected through purposive sampling and were randomly assigned to three groups (two experimental groups and one control group). The experimental groups received a 10-session intervention of 90 minutes each based on positive psychology, while the control group received no intervention. The research instruments included the Academic Well-Being Questionnaire developed by Tuominen-Soini and Salmela-Aro (2012), the Academic Vitality Scale by Martin and Marsh (2006), and the short form of the Achievement Emotions Questionnaire by Pekrun et al. (2005).Findings: The data were analyzed using covariance analysis through SPSS-26 software. The results showed that the positive psychology intervention was effective in improving students’ academic well-being (P < .05). The intervention also had a significant effect on students’ academic emotions (P < .05). Furthermore, the intervention was found to be effective in enhancing academic vitality in lower secondary school students (P < .05).Conclusion: Therefore, it is recommended that positive psychology interventions be utilized to improve academic well-being, academic vitality, and academic emotions.